PENGARUH PENDAPATAN ASLI DAERAH (PAD), BELANJA MODAL DAN SISA LEBIH PEMBIAYAAN ANGGARAN (SILPA) TERHADAP KINERJA PEMERINTAH DAERAH KABUPATEN/KOTA PROVINSI SUMATERA SELATAN - Djuniar, Lis; Zuraida, Ida (Balance : Jurnal Akuntansi dan Bisnis, 2018)
This study aims to determine the effect of Regional Original Income, Capital Expenditures and More Budget Financing on the Performance of District / City Regional Governments in South Sumatra Province in 2012-2016 with a total sample of 75 samples. This type of research is associative research. The data used in this study are primary data and secondary data. Data collection methods used in this study use the documentation method. Data analysis in this study uses qualitative analysis. The results in this study can be concluded that the Regional Original Income does not affect the Performance of the District / City Regional Government of South Sumatra Province. Capital expenditure does not affect the performance of the Regency / City regional government of South Sumatra Province. More Budget Financing Remains negatively affect the performance of local governments. Simultaneously Regional Original Revenue, Capital Expenditures and More Budget Financing Remains simultaneously affect the Performance of Regency / City Regional Government of South Sumatra Province.This result shows that if there is an increase of the Budget Financing Remaining, the assessment of Local Government Performance has decreased and vice versa if there is a decrease in the Budget Financing Remaining then the performance of the Regency / City Regional Government of South Sumatra Province has increased.